2008
DOI: 10.1088/0957-4484/19/42/424020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin SiO2layers on Si(111): preparation, interface gap states and the influence of passivation

Abstract: An essential prerequisite for the successful application of Si/SiO(2) nanostructures in photovoltaics is the realization of well-defined and abrupt interfaces with low densities of interface gap states. Here, a complete in situ process from preparation and hydrogen passivation to interface gap state analysis by near-UV photoelectron spectroscopy without breaking ultrahigh vacuum (UHV) conditions is introduced. It is demonstrated that by RF plasma oxidation of Si(111) substrates with thermalized neutral oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…It has been demonstrated that structural abruptness is not inherent with an increase of the density of interface states [2]. The resulting oxide layer thickness can be adjusted in the range by appropriate variation of the oxidation time (5,…, 60 min), the substrate temperature (300,…, 600°C), and the plasma power (200,…, 600 W) [25].…”
Section: Wet-chemical Substrate Pre-treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that structural abruptness is not inherent with an increase of the density of interface states [2]. The resulting oxide layer thickness can be adjusted in the range by appropriate variation of the oxidation time (5,…, 60 min), the substrate temperature (300,…, 600°C), and the plasma power (200,…, 600 W) [25].…”
Section: Wet-chemical Substrate Pre-treatmentmentioning
confidence: 99%
“…4, curve 2). These extrinsic states, forming a Gaussian distribution in the lower half of the forbidden gap are caused by dangling bond defects (Si−) 2 (O−)Si• which are correlated with Si atoms of a lower state of oxidation, Si +1 [32]. The occurrence of oxygen backbonded Si dangling bond defects indicates that the surface is not completely hydrogen terminated.…”
Section: Influence Of Preparation-induced Substrate Surface Micro-roumentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, SPV allows the determination of surface band-bending and the recombination behavior [42,43]. It has been proven to be well-suited for the characterization of hydrogenated Si wafers, and ultrathin oxide nanolayers [44,45], as well as a-Si:H/c-Si interfaces [46].…”
Section: Introductionmentioning
confidence: 99%